Colonic delivery of film coated meloxicam tablets using natural polysaccharide polymer mixture (International Current Pharmaceutical Journal, 2012)
Now days natural polysaccharides are extensively used for the development of solid dosage forms for delivery of drug to the colon. The objective of the present study was to develop a site-specific drug, single unit formulation allowing targeted drug release in the colon. Solid unit dosage forms were prepared using polysaccharides or synthetic polymer included xanthan gum, pectin, chitosan and Eudragit-E. Meloxicam was used as a model drug. The prepared tablets were enteric coated with Eudragit-S 100 to give protection in the stomach. The coated tablets were tested in-vitro for their suitability as colon specific drug delivery systems. The dissolution data so obtained illustrates that enteric coated tablets containing 3% chitosan as a binder, showed only 12.5% drug release in the first 5 h, which is the usual upper gastrointestinal transit time, whereas, tablets prepared using xanthan gum as binder, were unable to protect drug release under similar conditions. Solid formulations containing pectin as a binder formed time-dependent release formulations. 28% drug release was observed in the usual upper gastrointestinal tract conditions, when used in a concentration of 5.92% in the tablets.DOI: http://dx.doi.org/10.3329/icpj.v1i9.11617 International Current Pharmaceutical Journal 2012, 1(9): 264-271